Determinants of household’s dietary diversity during the COVID-19 pandemic: A community-based study in rural Southwestern Bangladesh - Suvasish Das Shuvo; Tamanna Aktar; Asma Khatun; Md. Mohtasim Hasan; Tapon Kumar Das; Md Emran Hossain; Md. Sakhawot Hossain (PLoS ONE, 2025)
Background Inadequate dietary diversity is a significant challenge in public health for low-and middle-income countries, including rural communities in Bangladesh. These issues have intensified and become more tragic during the COVID-19 pandemic. This study evaluated the factors associated with household dietary diversity in rural Southwestern Bangladesh during the COVID-19 pandemic. Methods This cross-sectional study used a structured questionnaire to collect data from 310 respondents using face-to-face interviews. Household Dietary Diversity Score (HDDS) and sociodemographic characteristics were calculated from the Food and Nutrition Technical Assistance III Project (FANTA) guidelines and related studies. A multinomial regression model was performed to identify factors associated with HDDS during the COVID-19 outbreak. Result The HDDS status of rural Southwestern households decreased (60.3%) during the initial COVID-19 pandemic. Socioeconomic factors including gender, level of education, occupation, household monthly income, and family size of the household head were significantly associated with dietary diversity. Additionally, income condition (RRR:5.46, 95% CI:2.73–7.47 and RRR:4.85, 95% CI:2.48–7.24), and dietary diversity knowledge of the household head (RRR:5.46, 95% CI:2.73–7.47, and RRR:4.85, 95% CI:2.48–7.24) were significantly associated with low and moderate HDDS during the COVID-19 pandemic. Conclusion This study found that households become more vulnerable to inadequate dietary diversity due to poor socioeconomic status during the COVID-19 pandemic. Based on the findings, public health workers should ensure adequate food access and proper food distribution among rural households and communities in this crisis to mitigate these negative consequences.